2005
DOI: 10.1007/s10733-005-0079-1
|View full text |Cite
|
Sign up to set email alerts
|

Theoretic and Experimental Study of Photoprocesses in Substituted 4-Dicyanomethylene-4H-pyrans

Abstract: 1 Substituted 4-dicyanomethylene-4H-pyran (DCM) derivatives are widely used in quantum electronics and optoelectronics as active media of tunable lasers, emitting layers of organic light diodes [1,2], and nonlinearoptics media [3][4][5]. The active media based on substituted DCMs lase in the red spectral region in solutions and solid matrices [6,7], have high photochemical stability, and exhibit a broad emission band up to 120 nm. Their absorption and emission spectra practically do not overlap (the Stocks shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
2
7
0
Order By: Relevance
“…The peaks of the absorption spectra of DWK-2 and ZWK-2 are red shifted by 17 and 11 nm, respectively, compared to molecules with a single electron donor fragment. A similar red shift has been reported for the molecule with two electron donor fragments bis-DCM compared with DCM molecules with a single electron donor fragment [40]. It is observed that molecules with two electron donor fragments have a larger conjugation length.…”
Section: Absorption and Luminescence Propertiessupporting
confidence: 84%
“…The peaks of the absorption spectra of DWK-2 and ZWK-2 are red shifted by 17 and 11 nm, respectively, compared to molecules with a single electron donor fragment. A similar red shift has been reported for the molecule with two electron donor fragments bis-DCM compared with DCM molecules with a single electron donor fragment [40]. It is observed that molecules with two electron donor fragments have a larger conjugation length.…”
Section: Absorption and Luminescence Propertiessupporting
confidence: 84%
“…In pure solution, the dye exhibits a broad (full width at half maximum, fwhm, ~4600 cm −1 ), intense, and structureless band centered at 466 nm which is assigned to the S 1 (π*) ← S 0 (π) transition [35,46,47]. Additional high-energy absorption peaks located at 374 and 355 nm have been assigned to S 2 ← S 0 and S 3 ← S 0 transitions, respectively [35,46,47]. By the use of theoretical density functional theory (DFT) and complete active space self-consistent-field (CASSCF) approaches, it has been found that trans and cis DCM isomers possess comparable stabilities [47].…”
Section: Resultsmentioning
confidence: 99%
“…The active media based on substituted DCMs laser in the red spectral region in solutions and solid matrices have high photochemical stability and exhibit a broad emission band. Some DCMs possess nonlinear optical properties as optical radiation limiters 36–38.…”
Section: Computational Details and Methodologymentioning
confidence: 99%